Pengaruh Kelas Sosial, Harga, Promosi Dan Lokasi Terhadap Keputusan Pembelian Rumah (Studi Pada PT. Jawara Bangun Persada, Karangploso Malang) - Helga Dita Agustin; Eka Farida; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of social class, price, promotion, and location on the decision to purchase a study house at PT Jawara Bangun Persada, Karangploso, Malang. The sample used in this study were 58 respondents. The data analysis method used is quantitative data analysis. To solve the problem in this research, using validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classical assumption test. This study uses multiple linear regression analysis with the help of SPSS 25. The results of this study indicate that the result  of the statement of class Social, Harga, Promot ion and Location in the results of the Purchase Decision test show that only the Social Class variable has a negative and insignificant effect, while the Price, Promotion variable , and Location has a significant and significat effect on purchasing decision. Keywords: Social Class, Promotion, Price, Location, Developmet